Pengaruh Model Tokoh dalam Al-Qur’an Terhadap Kisah Inspiratif Islami “Yusuf Zulaikha: The Greatest Love Story”: Analisis Sastra Bandingan - Ahmad Sirfi Fatoni (Matluba: Jurnal Pendidikan Bahasa dan Budaya Arab, 2024)
The character model was one of the studies in the comparative literature. One of the character models was the character model taken from the religious figure model. This study was a comparative literary study that had a different language and had an impression of influence between one work and another. This study used a comparative analysis of similarities using descriptive methods. This article examines the influence of the model of religious figures from the Arabic text of the Qur’an to non-Arabic literary works, the Islamic Inspirational Story "Yusuf Zulaikha: The Greatest Love Story". This research also looks at the author's creativity process in developing the data. The results of this study are: The first, the Islamic Inspirational Story "Yusuf Zulaikha: The Greatest Love Story" by Abd. Rahem was greatly influenced by the model of religious figures taken from the Qur'anic story, Yusuf. The Second, the author's creativity process was by discussing and reading other literature, and the form of the writer's creativity lies in the systematic writing, narration of storytelling, and the addition of information from the intrinsic and extrinsic elements of a story.